Calcaneonavicular coalition resection : technical tip - Juncay, Mercedes; Sposeto, Rafael; Godoy-Santos, Alexandre; Fernandes, Túlio (Journal of the Foot & Ankle, 2020)
Tarsal coalition is an abnormal connection between tarsal bones, caused by an embryogenic failure. Its most common forms are calcaneonavicular and talocalcaneal coalition, which are present in 53% and 37% of the cases, respectively. The onset of symptoms is related to tarsal bone ossification, and mean age for this event is estimated at 16 years for calcaneonavicular coalition. Surgical treatment is indicated for patients who did not improve symptoms with conservative treatment. The aim of this study is to present a surgical technique as a treatment option for resection of calcaneonavicular coalition associated with abnormal cuboid-navicular joint. Level of Evidence V; Therapeutic Studies; Expert Opinion.